2012
DOI: 10.1128/mcb.00374-12
|View full text |Cite|
|
Sign up to set email alerts
|

Mediator Promotes CENP-A Incorporation at Fission Yeast Centromeres

Abstract: dAt Schizosaccharomyces pombe centromeres, heterochromatin formation is required for de novo incorporation of the histone H3 variant CENP-A Cnp1 , which in turn directs kinetochore assembly and ultimately chromosome segregation during mitosis. Noncoding RNAs (ncRNAs) transcribed by RNA polymerase II (Pol II) directs heterochromatin formation through not only the RNA interference (RNAi) machinery but also RNAi-independent RNA processing factors. Control of centromeric ncRNA transcription is therefore a key fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 64 publications
1
25
1
Order By: Relevance
“…Consistent with our conclusions, a very recent study by Zhu and colleagues [45], published during the writing of this article, reports an accumulation of centromeric non-coding RNA and reduced processing of the dh repeat transcript into siRNA in a med20Δ strain. In addition, an independent large-scale epistasis map revealed genetic interactions between subunits of the Mediator and RNAi and heterochromatin components [29].…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with our conclusions, a very recent study by Zhu and colleagues [45], published during the writing of this article, reports an accumulation of centromeric non-coding RNA and reduced processing of the dh repeat transcript into siRNA in a med20Δ strain. In addition, an independent large-scale epistasis map revealed genetic interactions between subunits of the Mediator and RNAi and heterochromatin components [29].…”
Section: Discussionsupporting
confidence: 92%
“…Recently, two reports showed that MHD was important for heterochromatin formation at pericentromeres [34], [35]. However, there are several discrepancies between their data and ours.…”
Section: Discussioncontrasting
confidence: 72%
“…Indeed, recent reports suggest a negative role of MHD subunits (Med18 and Med20) in heterochromatic transcription, based on the observation of an increase in the transcription of pericentromeric ncRNA in Mediator mutants [34], [35]. However, it is difficult to state conclusively whether the observed increase is due to the direct effects of the absence of Mediator because it is also possible that the deletion of Mediator subunits causes disruption of the heterochromatin, which secondarily induces an increase in transcription.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with this, loss of factors required for the reassembly and stabilization of H3 nucleosomes behind RNA Pol II, such as FACTand Clr6-complex II, promotes CENP-A assembly in place of histone H3 in noncentromeric regions of the genome . Moreover, some subunits of the Mediator complex are required for CENP-A Cnp1 localization, and the reduced levels of CENP-A Cnp1 in Mediator mutants can be suppressed by RNA Pol II inhibitors (Carlsten et al 2012). This finding suggests that proper levels of centromeric transcription are critical to ensure inheritance of the functional centromere state.…”
Section: It Is Currently Unknown What Restricts Cenp-amentioning
confidence: 99%